Patient reported experience of the burden of neuroendocrine tumors and impact of eSHINE Patient Support Program on patient quality of life. (3rd November 2020) - Wakelin, Kate
Abstract: Aim: Neuroendocrine tumors (NETs) are an uncommon cancer and difficult to diagnose and treat. Treatment is complicated by debilitating side effects, impacting quality of life. This Australia‐wide survey aimed to increase our understanding of the impact and burden of NETs on patient quality of life (QoL) and to assess the benefit of a patient support program (eSHINE). Method: Consented patients from the eSHINE mailing list ( n  = 267) were invited to participate in an electronic self‐reported survey comprising 29 questions on clinical characteristics, diagnosis, sociodemographics, impact of living with NETs and benefits of a patient support program. No formal sample size was calculated. All analyses were descriptive. Results: A total of 144 participants (54%) responded. A total of 129 (48%) completed all questions. Approximately half of respondents were female, from metropolitan and rural areas, aged over 65 years and had a primary diagnosis of gastrointestinal NETs. Fifty‐eight percent had been diagnosed over 5 years ago. Twenty‐seven percent reported seeing four or more healthcare professionals prior to being diagnosed. Living with NETs had a large impact on patients' QoL. 83.5% reported fatigue, 76% felt their emotional health was impacted by NETs and 75% reported reduced ability to participate in leisure activities. Access to a supportive network to manage and treat NETs was extremely important to participants. Eighty‐five percent of respondents reported the eSHINE program had a positive impact on their QoL. Conclusion: Patients value support from healthcare professionals and patient support programs such as eSHINE in managing NETs. The eSHINE Patient Support Program has a positive impact on patient QoL.